A randomized, double‐blind clinical trial to evaluate the blood pressure lowing effect of low‐sodium salt substitution on middle‐aged and elderly hypertensive patients with different plasma renin concentrations. Issue 2 (29th December 2021) - Che, Li; Song, Wei; Zhang, Ying; Lu, Yan; Cheng, Yunpeng; Jiang, Yinong
Abstract: This study aimed to evaluate the blood pressure (BP) lowing effect of low‐sodium (LS) salt substitution and how the effect influenced by plasma renin concentration (PRC) on middle‐aged and elderly hypertensive patients. Three hundred fifty‐two hypertensives were randomized at a 1:1 ratio into a LS group and a normal salt (NS) group. We compared intergroup changes observed in office blood pressure measurement (OBPM) and home blood pressure measurement (HBPM). Then, all patients in LS group were divided into tertiles according to baseline PRC, aldosterone concentration, and aldosterone/renin ratio (ARR), and changes in OBPM and HBPM were compared across the three tertile subgroups. Follow‐up surveys were completed by 322 patients. The intergroup net reduction in systolic OBPM, systolic HBPM, and diastolic HBPM was −6.6, −4.6, and −2.3 mmHg, respectively (all P  < .05), and −1.8 mmHg in diastolic OBPM ( P  = .068). There was a more significant reduction in OBPM and HBPM among the low baseline PRC subgroup than among the high PRC subgroup. There were no significant differences in the changes in OBPM and HBPM between the three subgroups when grouped according to baseline aldosterone concentration. The reduction in OBPM and HBPM in the high tertile of ARR was larger than that in the low tertile subgroup. LS salt substitution is effective in reducing systolic OBPM, systolic HBPM, and diastolic HBPM in middle‐aged and elderly hypertensive patients. LS salt substitution may offer a non‐pharmaceutical therapy for hypertensive patients. Baseline PRC may be a marker to predict BP response after salt restriction.